PENGGUNAAN QR CODE DALAM PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI DIGITAL BERWAWASAN LINGKUNGAN - Laily Hidayati (Jurnal Lingkar Mutu Pendidikan, 2022)
QR Code is one of the innovations in developing digital literacy media in identifiying plant in scholls. The purpose of this study was to determine the response of students about the development of digital literacy media as an innovation to identify plants in schools. Meanwhie, students responses were obtained from questionnaire analysis by 30 students of SMP Negeri 1 Jatiroto. The results of the instrument test showed that the QR Code as a Digital Literacy Innovation for Plant Identifications that was developed showed positive results with a percentage yield of 93,27%. This means that the QR Code as adigital literacy innovation in identifying school plants can be used in leraning and supports digital literacy with an environmental perspective. Keywords: Use of QR Code, Discovery Learning, Digital Literacy, Environmentally minded